Road Toward a New Model of Care for Idiopathic Pulmonary Fibrosis in the Lazio Region - Di Bidino, Rossella; Rogliani, Paola; Sebastiani, Alfredo; Ricci, Alberto; Varone, Francesco; Sgalla, Giacomo; Iovene, Bruno; Bruni, Teresa; Flore, Maria Chiara; D'Ascanio, Michela; Cavalli, Francesco; Savi, Daniela; et al. (Frontiers in Medicine, 2022)
• A timely, confirmed diagnosis of Idiopathic Pulmonary Fibrosis (IPF) has a significant impact on the evolution of the disease. • The current model of care in the Lazio region (in Italy) was assessed on the basis of real-world data provided by the four reference centers responsible for diagnosing and treating IPF. The 5-year, population-based, retrospective longitudinal study provided the data that is at the basis of the current proposal and has been shared with regional decision makers. • A clinical and therapeutic pathway (DTCP) must be defined and based on four pillars: GPs, pulmonologists, IPF centers, and telemedicine. Each must play a role within a sort of hub-and-spoke model. IPF centers remain the hubs, while spokes are identified in trained GPs and pulmonologists.